1982
DOI: 10.1180/minmag.1982.046.338.14
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide mineralogy of a hydrothermal assemblage on Santorini Island, Aegean Sea

Abstract: ABSTRACT. Basement rocks of Santorini have been locally impregnated by iron oxides and other minerals. The hydrothermal fluids which caused the mineralization have extensively altered the impregnated rocks, but left granditic garnets in these unaffected.M6ssbauer spectroscopy and differential X-ray diffraction show that the iron oxides present are goethite and hematite in a ratio of about 2: 1. The presence of hematite indicates that these minerals formed, directly from a hydrothermal phase, at higher temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Murad & Schwertmann (1983) came to similar conclusions based on the dependence of the magnetic hyperfine field on Al substitution and crystallinity. It has also been suggested that Si impurities will have similar consequences (Murad, 1982). PDF analysis shows clear indications of a reduced crystallinity of sample B (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Murad & Schwertmann (1983) came to similar conclusions based on the dependence of the magnetic hyperfine field on Al substitution and crystallinity. It has also been suggested that Si impurities will have similar consequences (Murad, 1982). PDF analysis shows clear indications of a reduced crystallinity of sample B (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Mössbauer spectroscopy of polar corundum GaFeO 3 at ambient temperature and pressure confirms the long-range magnetic order demonstrated at room temperature by neutron diffraction (Figure d with fitted parameters shown in Table ). The absorption pattern is clearly decomposed into a combination of two magnetically ordered sites with average hyperfine fields of 39.48 and 33.09 T, respectively (the larger of the two being close to that of Goethite with its transition temperature of ∼400 K), which account for 91.09(2) % of the fitted area with the remainder assigned to one asymmetric paramagnetic doublet accounting for 8.91(2) % of the fitted area, which is a dynamic line shape resulting from the proximity of the Néel temperature. The two main sites exhibit significant static hyperfine field distributions with widths of 0.2–0.3 T. The fitted isomer shift (IS) of 0.25 mm/s and quadrupole splitting of 0.19 mm/s are consistent with Fe 3+ , but the IS is smaller than expected for a typical octahedral coordination in an oxide, which may be due to the high degree of static disorder in the system.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic structure has been studied by various techniques including Mössbauer spectroscopy, , neutron diffraction, susceptibility measurements, , and positron annihilation lifetime spectroscopy . The Néel temperature ( T N ) for the antiferro- to paramagnetic transition is as high as 130 °C for pure materials 12,16 but drops below room temperature as the level of cation doping (by cations such as Al 3+ ) or iron vacancies increases and/or crystallite size decreases. ,, A decrease in T N is also observed for materials with higher concentration of iron vacancies.…”
Section: Introductionmentioning
confidence: 99%